Efektifitas Pendidikan Kesehatan Makanan Pendamping ASI (MP-ASI) Terhadap Peningkatan Pengetahuan Ibu Dalam Pencegahan Stunting: Effectiveness of Complementary Food Health Education for Breast Milk (MP-ASI) in Increasing Mother's Knowledge in Stunting Prevention - Prabowo, Bayu; Wardani, Ratna (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Stunting is a syndrome of linear growth failure that can cause disturbances in physical growth, decreased neurodevelopment and cognitive function, as well as an increased risk of chronic diseases in adulthood which can cause morbidity and mortality in children. This study aims to analysed the effectiveness of providing health education regarding MP-ASI to increase mothers' knowledge in preventing stunting in children. Methods: This research uses a pre-experimental method with a one-group pre and post-test design. The population in this study were all mothers who had toddlers under 5 years of age. The sample size was 30 mothers taken using the total sampling technique. The instrument used in this research was a questionnaire on maternal knowledge of stunting. Data were analysed using the Wilcoxon signed rank test, with a significance level of ≤ 0.05. There is a difference in the level of mothers' knowledge about preventing stunting in children under 5 years of age before and after the intervention of providing health education regarding MP-ASI with a value of p= 0.000.